Uma análise do emprego formal nos setores industrial e de serviços brasileiros - Conceição, Luciano Nakabashi; Scatolin, Fábio Dória; Cruz, Márcio José Vargas da; Porcile, Gabriel (Revista Economia & Tecnologia, 2007)
*